Arabic mystery literature in the novels Hukumat al zil and Awdat alghaib by Monther Alkabbani An analytical study - Noora, T C (MES Mampad College, University of Calicut, 2025)
The Kuwaiti novel has witnessed a remarkable development since its inception, influenced by the social and economic transformations the country has undergone, especially after the discovery of oil. In its early stages, the Kuwaiti novel focused on traditional values and social changes but soon expanded to address deeper issues such as national identity, class struggle, women's role, and cultural transformations. Taleb Al-Refai is considered one of the most prominent Kuwaiti novelists who managed to present an accurate and vivid picture of Kuwaiti society through his literary works. His novels reflect social, economic, and cultural transformations in Kuwait, dealing with issues like class conflict, family relationships, women's roles, national identity, and urban changes. Al-Refai adopts a realistic narrative style highlighting the contradictions between modernity and tradition, revealing the impact of economic changes, especially after the oil boom, on society’s structure and identity. This study discusses the rise and development of the Arabic novel in Kuwait through four main chapters: an introduction presenting the research goals, problem, and methodology; the first chapter reviews the history of Kuwaiti Arabic novels focusing on their stages and prominent writers; the second chapter provides a comprehensive study of Taleb Al-Refai’s life, ideas, important literary and cultural milestones, and his impact; the third chapter analyzes his literary features and narrative techniques; and the fourth chapter highlights Kuwaiti society as depicted in his novels, discussing culture between heritage and modernity, society’s customs and traditions, class conflicts, intellectual problems, marriage and divorce, and women's social conditions. This chapter integrates literary and social aspects present in Al-Refai's works. The study concludes that the Kuwaiti novel began evolving since the 1960s, mirroring social reality after oil discovery, later including political and ideological concerns, which enhanced its literary status. Taleb Al-Refai’s rich and diverse literature reflects social and political transformations in Kuwait and the Arab world through innovative narrative techniques like time manipulation, symbolism, and mixing reality with fiction. His novels realistically portray Kuwaiti society from independence to the modern era, focusing on economic and demographic changes, conflicts between tradition and modernity, and social class issues.
Keywords: transformation; identity; tradition vs modernity; Taleb al refai; class struggle; narrative techniques